A bespoke reagent free amperometric chloride sensor for drinking water - Guo, Y; Compton, RG (Royal Society of Chemistry, 2021)
Chloride quantification is important in drinking water quality control. A bespoke, rapid and reagent free electrochemical method is reported for a simple and accurate chloride sensor specifically for mineral water without the need for added electrolyte. The voltammetry used embraces first the reduction of oxygen to clean and activate the electrode surface and ensure reproducibility without the requirement for any mechanical polishing, followed by silver chloride formation and stripping. A linear correlation was found with silver chloride stripping peak currents and chloride concentrations within the range of 0.4 mM to 3.2 mM on a silver macro disc electrode. The chloride concentrations in two different mineral water samples were measured giving excellent agreement with independent analysis.